2021
DOI: 10.1186/s13690-021-00642-z
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy complications, substance abuse, and prenatal care predict birthweight in adolescent mothers

Abstract: Background Reduced birthweight is associated with adverse physical and mental health outcomes later in life. Children of adolescent mothers are at higher risk for reduced birthweight. The current study aimed to identify the key risk factors affecting birthweight in a well-characterized sample of adolescent mothers to inform preventive public health efforts. Methods Sixty-four adolescent mothers (≤ 21 years of age) provided detailed data on pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
1
4
0
1
Order By: Relevance
“…In terms of associated factors, the study found that women with a history of obstetric complications were more likely to engage in risky substance use during the perinatal period (AOR = 1.722, 95%: 1.022–2.902). This is consistent with other studies conducted in Germany [ 13 ], in the United States [ 41 ], in South Africa [ 42 ], and in Ethiopia [ 10 ]. This suggests that stress and anxiety related to previous complications may lead some women to turn to substances as a coping mechanism.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In terms of associated factors, the study found that women with a history of obstetric complications were more likely to engage in risky substance use during the perinatal period (AOR = 1.722, 95%: 1.022–2.902). This is consistent with other studies conducted in Germany [ 13 ], in the United States [ 41 ], in South Africa [ 42 ], and in Ethiopia [ 10 ]. This suggests that stress and anxiety related to previous complications may lead some women to turn to substances as a coping mechanism.…”
Section: Resultssupporting
confidence: 93%
“…Substance use during the perinatal period is linked to adverse outcomes such as miscarriage, intrauterine growth restriction, early labor, and intrauterine fetal demise [ 16 ]. It is strongly associated with reduced birth weight [ 13 , 17 ], inadequate parenting [ 14 ], stillbirth, spontaneous abortion, premature birth, and intrauterine growth retardation [ 1 , 10 , 17 , 18 ]. Cigarette smoking and prenatal alcohol exposure are the leading preventable causes of pregnancy-related morbidity, mortality, and developmental problems [ 16 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant effects of a risky pregnancy on the child's growth and physical and mental health have been demonstrated (4). Pregnancy complaints during pregnancy has a significant impact on the physical and mental health of the mother and the way she communicates with her child after childbirth (5).…”
Section: Introductionmentioning
confidence: 99%
“…From the medical point of view, adolescent pregnancies have a higher risk of complications and there is evidence that maternal mortality in the 13-19 age group is two times more compared to the 20-34 age group [7]. Regarding maternal complications, higher rates of anemia, pregnancy-induced hypertension and preeclampsia have been reported [8]. There is also evidence of higher rates of fetal complications, such as fetal growth restriction (FGR), prematurity, miscarriage, and fetal death [9,10].…”
Section: Introductionmentioning
confidence: 99%